2020
DOI: 10.1080/10494820.2020.1799020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how student motivation relates to acceptance and participation in MOOCs

Abstract: In recent years, MOOCs have become firmly established as valid e-learning environments and, as such, have been developed by many universities using different types of platform. Given the voluntary nature of MOOC enrollment, motivation is crucial to our understanding of why students register for and complete these courses. The present study explores the motivations that characterize MOOC participants and how they relate to technology acceptance variables (data collected via questionnaires) and participation var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
(110 reference statements)
1
17
0
9
Order By: Relevance
“…The main motives behind enrolling in MOOCs include intrinsic and extrinsic motivation (Glynn et al, 2011;Milligan & Littlejohn, 2017;Zheng et al, 2015). For example, Romero-Frías et al (2020) found that MOOC learners showed a high level of intrinsic motivation, while at the same time, certain extrinsic motivations also played a role in their MOOC learning. Barba et al (2016) found a positive relationship between learner motivation, participation, and performance in MOOCs.…”
Section: Motivations In Moocsmentioning
confidence: 99%
“…The main motives behind enrolling in MOOCs include intrinsic and extrinsic motivation (Glynn et al, 2011;Milligan & Littlejohn, 2017;Zheng et al, 2015). For example, Romero-Frías et al (2020) found that MOOC learners showed a high level of intrinsic motivation, while at the same time, certain extrinsic motivations also played a role in their MOOC learning. Barba et al (2016) found a positive relationship between learner motivation, participation, and performance in MOOCs.…”
Section: Motivations In Moocsmentioning
confidence: 99%
“…Multi-Group Analysis has been used for structural model assessment in three studies . Romero-Frías et al (2020) have conducted confirmatory factor analysis using LISREL and then applied cluster analysis to understand student motives for MOOCs. Dikcius et al (2020) have used logistics regression to understand the role of social interactions and gamification on MOOC satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…However, different findings were reported by Romero-Frí as et al (2020). Correlation analysis was used to explore how students' motivation affected their participation in MOOCs.…”
Section: Motivation Of Studentsmentioning
confidence: 99%
“…To sum up, scholars identified students' motivations to enrol or to complete a MOOC as intrinsic motivation, extrinsic motivation, and social motivation. Studies indicated that intrinsic factors drove all learners to study MOOCs, but not all learners reported extrinsic motivation (Romero-Frí as et al, 2020). Students who studied sciences, technology, engineering, and mathematics (STEM) courses may have had stronger extrinsic motivation than students who studied other topics (Shapiro et al, 2017).…”
Section: Motivation Of Studentsmentioning
confidence: 99%
See 1 more Smart Citation